2019
DOI: 10.1074/jbc.ra118.006987
|View full text |Cite
|
Sign up to set email alerts
|

The copper-sensing transcription factor Mac1, the histone deacetylase Hst1, and nicotinic acid regulate de novo NAD+ biosynthesis in budding yeast

Abstract: Edited by John M. Denu NADH (NAD ؉) is an essential metabolite involved in various cellular biochemical processes. The regulation of NAD ؉ metabolism is incompletely understood. Here, using budding yeast (Saccharomyces cerevisiae), we established an NAD ؉ intermediate-specific genetic system to identify factors that regulate the de novo branch of NAD ؉ biosynthesis. We found that a mutant strain (mac1⌬) lacking Mac1, a copper-sensing transcription factor that activates copper transport genes during copper depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(59 citation statements)
references
References 64 publications
(87 reference statements)
4
55
0
Order By: Relevance
“…Hst1 does not bind the DNA directly but interacts with Rfm1 and Sum1 to form a repressor complex. Mac1, which was previously characterized as a copper‐sensing transcription factor, has been shown to also be involved in regulation of BNA genes, together with Hst1 (Bedalov et al, ; James Theoga Raj et al, ; Laurenson & Rine, ; McCord et al, ). When NA is abundantly available, NA salvage metabolism is preferred over use of the de novo biosynthetic pathway, which is repressed by Hst1 (Bedalov et al, ; James Theoga Raj et al, ).…”
Section: Vitamins That Act As Metabolic Precursors For Cofactor Biosymentioning
confidence: 99%
See 1 more Smart Citation
“…Hst1 does not bind the DNA directly but interacts with Rfm1 and Sum1 to form a repressor complex. Mac1, which was previously characterized as a copper‐sensing transcription factor, has been shown to also be involved in regulation of BNA genes, together with Hst1 (Bedalov et al, ; James Theoga Raj et al, ; Laurenson & Rine, ; McCord et al, ). When NA is abundantly available, NA salvage metabolism is preferred over use of the de novo biosynthetic pathway, which is repressed by Hst1 (Bedalov et al, ; James Theoga Raj et al, ).…”
Section: Vitamins That Act As Metabolic Precursors For Cofactor Biosymentioning
confidence: 99%
“…Mac1, which was previously characterized as a copper‐sensing transcription factor, has been shown to also be involved in regulation of BNA genes, together with Hst1 (Bedalov et al, ; James Theoga Raj et al, ; Laurenson & Rine, ; McCord et al, ). When NA is abundantly available, NA salvage metabolism is preferred over use of the de novo biosynthetic pathway, which is repressed by Hst1 (Bedalov et al, ; James Theoga Raj et al, ). In S. cerevisiae , NAD + metabolism is regulated together with phosphate and purine nucleotide metabolism, although the exact mechanisms remain uncharacterized (Lu & Lin, ; Pinson, Ceschin, Saint‐Marc, & Daignan‐Fornier, ).…”
Section: Vitamins That Act As Metabolic Precursors For Cofactor Biosymentioning
confidence: 99%
“…Therefore, the cell must maintain these metabolites and their flux in a controlled manner. We do not fully understand all the mechanisms by which the cell can sense and tune these metabolites, but some known NAD + homeostasis regulatory mechanisms include transcriptional control, feedback inhibition, nutrient sensing, and enzyme or metabolite compartmentalization [1,31,34,35,[37][38][39][40][41][42].…”
Section: Nad + Biosynthesis Pathwaysmentioning
confidence: 99%
“…Because Hst1 activity is dependent on NAD + , NAD + depletion results in transcription activation of the de novo pathway. A recent study showed that the copper-sensing transcription factor Mac1 appeared to work in concert with Hst1 to repress BNA genes [34].…”
Section: Nad + Biosynthesis Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation